Kinetics of Enolisation of Acetophenone and p-Bromoacetophenone: Comparative Studies - Swati Malhotra; Dipika Jaspal (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
Biomolecules (Amino Acids) have been used as catalysts for the study of kinetics involved in enolosation of acetophenone and p-bromoacetophenone, and comparative study has been carried out. The process of enolisation was studied by halogenations reactions using iodine. The stoichiometery was determined in each case and the kinetic reactions were carried out to study the effect of catalyst and temperature. The enolisation process was investigated as a bimolecular reaction. The rate of enolisation was of the order p- Bromoacetophenone > Acetophenone depending on the type of substituent. The process was investigated to follow Arrhenius equation. Values for various thermodynamic parameters like Entropy (∆S≠) and Enthalpy (∆H≠) were found to be -2.126 e.u. & -10.88 e.u. and 19.06 K. cal mol-1 & 19.01 K. cal mol-1 for acetophenone and p-bromoacetophenone respectively. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)